Economic efficiency of willow, poplar and black locust production using different soil amendments. (November 2017) - Stolarski, Mariusz J.; Olba-Zięty, Ewelina; Rosenqvist, Håkan; Krzyżaniak, Michał
Abstract: Profitability of biomass production is the main condition to be fulfilled for farmers to be more interested in growing short rotation woody crops (SRWC). The aim of this study was to assess the cost and economic efficiency of production of chips from three SRWC species (willow, poplar, black locust) depending on the soil amendment method, biomass prices and the transportation distance to the end user. The economic analysis assessed the cost of dry chips and unit energy production, revenue, discounted pay-back period, net present value and internal rate of return. In the base scenario the highest revenue 292 € ha −1 year −1 was found for willow amended with lignin. The best revenue for poplar (194 € ha −1 year −1 ) was achieved when the crop was fertilised with mineral fertiliser and amended with lignin. No options for black locust were profitable. Other economic indices were the best in the production of willow as well. The change in the biomass price and transport distance influenced the revenue in the production of all species. Our study has indicated the importance of the right choice of species and method of soil amendment, as this determined the biomass yield and it had a great effect on the cost of chip production and the amount of revenue gained from such production. Highlights: Species and method of soil amendment had a great effect on the economic indices. Willow had the highest net present values and internal rates of return. The cost of wood chips production varied from 48.9 to 198.3 € Mg −1 d.m. The cost of delivered 1 GJ in wood chips ranged from 2.5 to 10.2 € GJ −1 . Biomass price and transport distance had a large effect on the revenue.